201k views
8 votes
Explain to solve
3(×+4)-1=23

User Joakimbeng
by
5.2k points

2 Answers

5 votes

Answer:

3(x+4)-1+1=23+1

add 1 to both sides

3(x+4)=24

divide both sides by 3


(3(x+4))/(3) =(24)/(3)

x+4=8

x+4-4=8-4

subtract 4 from both sides

x=4

Explanation:

User Silentbob
by
4.5k points
10 votes

Answer:

x = 4

Explanation:

3 ( x + 4 ) - 1 = 23

First solve the brackets.

3x + 12 - 1 = 23

3x + 11 = 23

Now take 11 to the other side n solve it.

3x = 23 - 11

3x = 12

Now divide both sides by 3.

3x/3 = 12/3

x = 4

Hope this helps you :-)

Let me know if you have any other questions :-)

Have a nice day !!!

User ScrollerBlaster
by
5.3k points